Hubungan Boredom dengan Self-Regulated Learning Siswa SMK Jakarta dalam Kegiatan Pembelajaran - Amalia, Lulu; Fitniwilis, Fitniwilis; Utami, Rismar Julia; Oktarini, Ira (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to examine the relationship between boredom and self-regulated learning (SRL) in vocational high school students in Jakarta. Boredom is a feeling of displeasure or boredom that arises when someone feels that the activity being done is not interesting, monotonous, or meaningless. While Self-Regulated Learning is a process in which someone actively manages and controls their own learning process. High levels of boredom during learning are a significant challenge that reduces student motivation and engagement and has a negative impact on their SRL abilities. SRL itself includes (indicators) metacognitive abilities, self-motivation management and active behavior. The type of research used is quantitative correlational with statistical tests using Spearman Rank to measure the relationship between boredom variables and SRL. Respondents were obtained from several vocational high schools in the Jakarta DK area with the focus of this study on aspects of boredom such as disengagement, high arousal, low arousal, inattention, and time perception. And see its relationship with aspects of Self-Regulated Learning including metacognitive abilities, motivation in learning, and active behavior in learning activities. The results of the Spearman Rho test showed a strong and significant negative correlation between boredom and SRL. It has the interpretation meaning that the higher the student's SRL ability, the lower the level of boredom experienced. Detailed analysis also revealed a significant negative relationship between all aspects of boredom and SRL components. These findings confirm that high boredom inhibits students' cognitive and emotional involvement, thereby reducing the effectiveness of learning and academic achievement. Therefore, the development of SRL is the main strategy in reducing boredom and improving the quality of learning. This study provides important implications for educators to apply varied, humanistic learning methods that support students' psychological safety so that they can learn in a balanced emotional state and be actively involved in the teaching and learning process. Thus, it is hoped that the learning atmosphere will be more interesting, challenging, and relevant, thereby increasing motivation and students' independence in learning.